1959
DOI: 10.1136/hrt.21.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Infundibular Stenosis Complicating Simple Pulmonary Valve Stenosis

Abstract: Pulmonary valvotomy by the closed transventricular technique was introduced as an alternative to the Blalock-Taussig operation in Fallot's tetralogy (Brock, 1948) and for relief of pulmonary stenosis in the presence of a closed ventricular septum (Brock and Campbell, 1950). In Fallot's tetralogy, at least until closure of the ventricular septal defect became feasible, some residual pulmonary stenosis was considered desirable. With a normal aortic root, however, complete relief of the stenosis was sought. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1960
1960
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Inadequate enlargement of the valve orifice was usually blamed for poor results when closed valvotomy was the only practicable procedure (Swan, Cleveland, Mueller, and Blount, 1954 (Dilley et al, 1963), and that complete relief of the stenosis did not necessarily cause an immediate drop in gradient. Hypertrophic infundibular stenosis was recognized by Connolly, Lev, Kirklin, andWood in 1953 andindependently by Brock in 1955. Removal of the valvar obstruction allows the hypertrophied walls of the outflow tract to meet in systole and to cause an obstruction that may be little less severe than the previous one at valve level (Johnson, 1959). There is then no immediate relief of the right ventricular hypertension (McGoon andKirklin, 1958: Gerbode et al, 1960).…”
Section: -8mentioning
confidence: 99%
See 3 more Smart Citations
“…Inadequate enlargement of the valve orifice was usually blamed for poor results when closed valvotomy was the only practicable procedure (Swan, Cleveland, Mueller, and Blount, 1954 (Dilley et al, 1963), and that complete relief of the stenosis did not necessarily cause an immediate drop in gradient. Hypertrophic infundibular stenosis was recognized by Connolly, Lev, Kirklin, andWood in 1953 andindependently by Brock in 1955. Removal of the valvar obstruction allows the hypertrophied walls of the outflow tract to meet in systole and to cause an obstruction that may be little less severe than the previous one at valve level (Johnson, 1959). There is then no immediate relief of the right ventricular hypertension (McGoon andKirklin, 1958: Gerbode et al, 1960).…”
Section: -8mentioning
confidence: 99%
“…Hg and reported an incidence of 77 %. Johnson (1959) called it 'an infundibular gradient after valvotomy of 20 mm. Hg or more' and found that it followed 51 ,, of closed and 77% of open valvotomies.…”
Section: -8mentioning
confidence: 99%
See 2 more Smart Citations
“…
Persistence of a right-to-left interatrial shunt after relief of pulmonary valve stenosis is not necessarily related to the effectiveness of relief of the obstruction, but may reflect continued right ventricular dysfunction.When operative relief of pulmonary stenosis is too long delayed the results may be disappointing (Johnson, 1959;Campbell, 1959;Brock, 1961;McIntosh and Cohen, 1963). The present communication concerns six patients who were cyanosed following pulmonary valvotomy despite a normal right ventricular pressure both at rest and on exercise, and who were among a series of 56 patients with pulmonary valve stenosis operated upon under cardio-pulmonary bypass at Hammersmith and Brompton Hospitals between 1958 and 1963.
…”
mentioning
confidence: 96%